WORKSHOP ON CLASSROOM ACTION RESEARCH FOR ELEMENTARY SCHOOL TEACHERS IN SAMBAS REGENCY - Wardah, Wardah; Sri Rezeki, Yanti; Salam, Urai; Susilawati, Endang; Surmiyati, Surmiyati; Husin, Sy. (LPPM Univ. Ibn Khaldun Bogor, 2023)
To improve their competence and professionalism, teachers must always reflect on the learning process that they conduct, which is documented in the form of scientific papers called Classroom Action Research (CAR). The knowledge of teachers, especially elementary school teachers, regarding CAR is still very limited. Therefore, the PKM team of English Education Study Program lecturers carried out PKM activities on CAR. The purpose of this activity was to provide teachers with an understanding of the importance of CAR and how to conduct it. The activity was carried out using lecture, question and answer, and discussion methods. This activity took place for two days and was attended by 50 representatives of elementary school teachers in Sambas Regency. The results of the activity showed that the teachers were very enthusiastic and actively asked questions during the presentation and actively participated in group discussions. From the discussions and presentations, it was found that elementary school teachers in Sambas Regency were able to reflect on their classroom teaching to identify problems encountered in class, found the causes and solutions to the problems.